Epidemiological, clinical, and geographical characterization of Leprosy in the County of Santarém-Pará: Insights for effective control and targeted intervention. - Edson Jandrey Cota Queiroz; Ingrid Nunes da Rocha; Lívia de Aguiar Valentim; Thiago Junio Costa Quaresma; Zilmar Augusto de Souza Filho; Sheyla Mara Silva de Oliveira; Franciane de Paula Fernandes; Caroline Gomes Macedo; Tatiane Costa Quaresma; Waldiney Pires Moraes (PLoS Neglected Tropical Diseases, 2024)
Leprosy is an infectious disease characterized by slow and chronic evolution, caused by Mycobacterium leprae and or Mycobacterium lepromatosis, an intracellular alcohol-acid-resistant (BAAR) bacillus. The objective of this study was to provide an epidemiological, clinical, and geographic characterization of leprosy in the city of Santarém-Pará during the period 2011-2020. A cross-sectional, descriptive, and quantitative approach was used, employing maps and tables to illustrate clinical and epidemiological variables, including: sex, age, race, area of residence, operational classification, clinical form, number of skin lesions, number of affected nerves, and health units. During the analyzed period, 581 cases of leprosy were diagnosed, resulting in the following cumulative incidence rates: male (60%); age over 15 years (94%); urban area (73%); multibacillary (74%); borderline form (46%); skin lesions greater than 5 (34%); and no nerves affected (68%). In the urban perimeter, a higher cumulative incidence of cases was observed in the central area with 133 cases. However, the health unit reporting the largest number of cases belonged to the southern area, specifically the Basic Health Unit of Nova República, with 48 cases. This study highlights the need to characterize the nuances of leprosy and its variability within the urban environment, according to different areas. Further research is essential to inform the implementation of public policies aimed at addressing the population with the highest vulnerability index, thereby reducing leprosy rates in Santarém.